Expanding Labour’s Horizons: Union Organizing and Strategic Change in Canada - Yates, Charlotte AB (Just Labour, 2002)
How can unions arrest membership decline in an increasingly chilly climate? Unions across Canada have arrived at a common answer to this question; unions need to organize the unorganized, in particular reaching out to women, youth and people of colour. After a brief discussion of who is being organized by unions, this article turns to a discussion of innovations in union organizing strategies, including the virtue of rank and file activists and the B.C. Organizing Institute. The next challenge for unions is to keep newly organized workers as members. This depends on adequate representation of these members’ interests and opportunities for their participation in union affairs. The paper critically evaluates union efforts at reform of internal structures and collective bargaining practices. While organizing alone cannot secure the future of unions, it is a critical part of the process of the renewal of labour power. Comment les syndicats peuvent-ils freiner la diminution de leurs membres dans un climat qui leur est de plus en plus défavorable? Les syndicats du Canada entier ont trouvé une réponse commune à cette question : les syndicats doivent syndicaliser les personnes qui ne sont pas syndiquées, s’adressant particulièrement aux femmes, aux jeunes et aux personnes de couleur. Après avoir traité brièvement des personnes que recrutent actuellement les syndicats, cet article passe à un examen des stratégies innovatrices de recrutement syndical, y compris l’implication des militantes et militants de la base et l’institut du recrutement de la C-B. Le défi suivant que les syndicats doivent relever consiste à garder les membres nouvellement recrutés. Leur capacité d’y arriver dépend de l’adéquation de leur défense des intérêts de ces membres et des occasions qu’ils leur donnent de participer aux affaires syndicales. L’article comprend un examen critique des efforts faits par les syndicats pour réformer leurs structures internes et leurs pratiques de négociation collective. Le recrutement ne suffit pas à assurer l’avenir de syndicats, mais il est un élément critique du processus de renouvellement de leur pouvoir.